2022
DOI: 10.1177/0308518x221115439
|View full text |Cite
|
Sign up to set email alerts
|

Racial platform capitalism: Empire, migration and the making of Uber in London

Abstract: The critical platform studies literature has built a compelling picture of how techniques like worker (mis)classification, algorithmic management and workforce atomisation lie at the heart of how ‘work on-demand via apps’ actively restructure labour. Much of this emerging scholarship identifies that platform workforces are predominantly comprised of migrant and racially minoritised workers. However, few studies theorise migration and race as structuring logics of the platform model and the precarity it engende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 90 publications
(149 reference statements)
0
18
0
Order By: Relevance
“…These vignettes paint a complex fresco of a sector of the gig economy—food delivery—that, across the world, increasingly relies on migrant labour (Altenried 2021; Gebrial 2022; van Doorn and Vijay 2021). Based on qualitative data collected in Turin between August 2020 and June 2021, our article explores this variegated texture of social relations, interests, and practices.…”
Section: Introductionmentioning
confidence: 99%
“…These vignettes paint a complex fresco of a sector of the gig economy—food delivery—that, across the world, increasingly relies on migrant labour (Altenried 2021; Gebrial 2022; van Doorn and Vijay 2021). Based on qualitative data collected in Turin between August 2020 and June 2021, our article explores this variegated texture of social relations, interests, and practices.…”
Section: Introductionmentioning
confidence: 99%
“…Much like work games discussed above, the issue is that the resolution of worker tensions at the interpersonal level becomes an end in itself rather than questioning the structural forces that normalize the very reliance on precarious workers to begin with. Given that the vast majority of gig workers are migrants, racialized divisions of labour also remain unquestioned (Gebrial, 2022). Most personal shoppers suggested that on-demand delivery necessitates the use of cheap and precarious gig labour due to very low profit margins, risks and driver insurances, and logistical challenges of last mile delivery.…”
Section: Absorption Of Precarious Labour Into the Supermarketmentioning
confidence: 99%
“…While immigrant labour is equally prevalent in Toronto's taxi and ridehail sectors (Jeon et al 2019:20;Peticca-Harris et al 2020), ridehail drivers' perception in the public eye appears to be "less racialised" and, as a consequence, more positive. This, then, points to a pressing need to take into account the various stratifications-of race, citizenship, gender, and more-within emerging taxi-cum-ridehail labour forces (Hua and Ray 2018) and to systematically integrate struggles for the reclassification of drivers as employees into broader campaigns for migration and social welfare rights (Van Doorn et al 2022) in the context of a fast evolving "racial platform capitalism" (Gebrial 2022).…”
Section: Crafting a Legal Framework For Ubermentioning
confidence: 99%
“…What this contradiction amounts to, in short, is a zero‐sum game between worker‐friendly labour regulation on a local or regional scale and state competitiveness on a global one: an increase in the former means a reduction of the latter, and vice versa. Exempt for those more privileged groups of tech, “creative”, and other coveted workers enticed by custom‐tailored state immigration programmes (Mezzadra and Neilson 2013:137–142; Sharma 2019), the competition state tends to be a labour‐averse competition state; an observation that pertains even more so to business sectors—such as taxi and ridehailing industries across the North American continent—that almost exclusively rely on racialised, highly precarious immigrant workers from countries of the Global South (Gebrial 2022; Mathew 2008:8–10; Sundar 2012).…”
Section: State Space and The Geographies Of Ridehailing In Torontomentioning
confidence: 99%
See 1 more Smart Citation